Increase of infectious complications in ABO-incompatible kidney transplant recipients-a single centre experience - Habicht, Antje; Broeker, Verena; Blume, Cornelia; Lorenzen, Johan; Schiffer, Mario; Richter, Nikolaus; Klempnauer, Juergen; Haller, Hermann; Lehner, Frank; Schwarz, Anke (Nephrology Dialysis Transplantation, 2011)
Background. Due to the shortage of deceased donors ABO-incompatible (ABOi) living kidney transplantation has become a popular alternative to deceased kidney transplantation. In recent years, recipient desensitization with a combination of anti-CD20 treatment (rituximab), antigen-specific immunoadsorptions (IA) and intravenous immunoglobulin (IVIG), led to promising short-term and intermediate-term results. However, little is known about the impact of this intensified desensitization protocol on the risk of surgical and infectious complications. Methods. We retrospectively analysed 21 consecutive recipients who underwent ABOi renal transplantation. Pre-transplant desensitization included administration of rituximab (375 mg/m2), mycophenolate mofetil (MMF), tacrolimus and prednisolone 4 weeks prior of scheduled transplantation as well as IA and IVIG. Forty-seven patients who underwent ABO-compatible (ABOc) renal transplantation served as the control group. Medical records and electronic databases were reviewed for patient and graft survival, renal function, rate of rejections, viral and bacterial infections as well as for surgical complications (SCs) post-transplantation. Results. All patients showed an immediate graft function. During a mean follow-up of 15.7 ± 8.3 months (interquartile range 11.9) patient survival was 95 and 98% in the ABOi and ABOc group, respectively. Allograft survival and function, as assessed by serum creatinine levels and calculated glomerular filtration rate at 1 year, did not differ between ABOi and ABOc recipients. Furthermore, the rate of biopsy-proven acute rejections was comparable between the two groups. However, there was a trend towards more SCs within the ABOi group (29 versus 11%, non-significant). In addition, the rate of viral infections including cytomegalovirus, Herpes simplex virus, Varicella zoster virus and polyoma virus was significantly increased among the ABOi recipients (50 versus 21%; P = 0.038) despite comparable tacrolimus trough levels and MMF and steroid doses. Conclusions. Our results, in line with the extended experience of other groups, demonstrate favourable short-term allograft survival and function after ABOi renal transplantation after desensitization with antigen-specific IA, IVIG and rituximab. However, the intensified desensitization was associated with an increased risk of infectious complications. This observation prompted us to briefly escalate the desensitization protocol in ABOi kidney recipients in our centre. © 2011 The Author.
CRIS-Team Scopus Importer:2020-11-12
Keywords: ABO incompatible; infectious complication; renal transplantation